2007
DOI: 10.2116/analsci.23.401
|View full text |Cite
|
Sign up to set email alerts
|

Rapid DNA Hybridization Analysis Using a PDMS Microfluidic Sensor and a Molecular Beacon

Abstract: A rapid DNA analysis has been developed based on a fluorescence intensity change of a molecular beacon in a PDMS microfluidic channel. Recently, we reported a new analytical method of DNA hybridization involving a PDMS microfluidic sensor using fluorescence energy transfer (FRET). However, there are some limitations in its application to real DNA samples because the target DNA must be labelled with a suitable fluorescent dye. To resolve this problem, we have developed a new DNA microfluidic sensor using a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Upon reasonable design, such conformational change may be applied for varying the local environment of fluorophores or nanomaterials, and therefore altering the emission properties of fluorescent systems. Compared to colorimetry, fluorescence approaches show more promising applications in measuring bio-interactions in aquatic environment because of the flexible ways in quantitative analysis with high sensitivity and wide response range (Chen et al, 2008b;Kim et al, 2007;Jung et al, 2007). Traditional organic dyes associate with the problem of narrow absorption, broad emission, photobleaching and so on, unable to meet the expectations.…”
Section: Fluorometric Assaymentioning
confidence: 99%
“…Upon reasonable design, such conformational change may be applied for varying the local environment of fluorophores or nanomaterials, and therefore altering the emission properties of fluorescent systems. Compared to colorimetry, fluorescence approaches show more promising applications in measuring bio-interactions in aquatic environment because of the flexible ways in quantitative analysis with high sensitivity and wide response range (Chen et al, 2008b;Kim et al, 2007;Jung et al, 2007). Traditional organic dyes associate with the problem of narrow absorption, broad emission, photobleaching and so on, unable to meet the expectations.…”
Section: Fluorometric Assaymentioning
confidence: 99%
“…Thus detection of hybridisation of target and probe in a microflow system, with suitable mixing, presents considerable advantages in terms of speed. Lee and co-workers (Yea et al 2006;Kim et al 2007) implemented a fluorescence resonance energy transfer (FRET) system in a PDMS microfluidic device with an ''alligator teeth'' structure for efficient mixing in otherwise laminar flow, shown in Fig. 14b.…”
Section: Fluorescence Detectionmentioning
confidence: 99%
“…Yea et al (2006) employed a system where both the target DNA and probe strands were labelled, and relative intensities yielded the fraction of hybridised DNA. To avoid the need to label the target DNA, Kim et al (2007) then employed a molecular beacon, shown in Fig. 14a, where one end of a single-stranded oligonucleotide has a fluorophore attached and the other end has a quencher attached.…”
Section: Fluorescence Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the microfluidic technology, the complete DNA hybridization assay-including sampling, hybridization reaction, incubation and washing-can be conducted directly on a microfluidic platform in a liquid flow format (i.e., the probe-target reaction (hybridization) occurs in the flowing liquid). Kim et al (2007) and Chen et al (2008) developed a rapid DNA assay in a microfluidic chip of alligator teeth-shaped microchannel network, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%